How's Life in Your Region? Measuring regional and local well-being for policy-meeting. - (:unkn) unknown (My University, 2014)
This report paints a comprehensive picture of well-being in the 362 OECD regions, by looking at some of the most important aspects that shape people's lives: jobs, income, housing, education, health, access to services, environment, safety and civic engagement. The report finds that the disparities in material conditions and quality of life are often greater among regions within the same country than they are across different countries. While on average people are richer, they live longer and they enjoy a better air quality than fifteen years ago, the intra-country gaps between the best- and worst-performing regions in terms of many well-being dimensions have been widening in many OECD countries. The report provides a common framework for measuring well-being at the regional level and guidance for all levels of government in using well-being measures to better target policies at the specific needs of different communities. The report draws from a variety of practical experiences from OECD regions and cities.
Keywords: Regionalplanung; Regionale Daten; Regionalpolitik; Regionalentwicklung; Indikator; Lebensbedingungen; Lebensqualität; Empirische Untersuchung; Internationaler Vergleich; Regionalvergleich